PROBLEMATIKA ISBAT NIKAH DALAM OPTIK PERUNDANG-UNDANGAN - Wahid Wahidullah; Ricky Khoirul Umam (JURIS (Jurnal Ilmiah Syariah), 2019)
The marriage certificate is the process of recording marriage to a marriage that is carried out on a legal basis and has not been approved by the legality or marriage certificate of the marriage. The purpose of the marriage ratification is to obtain legal certainty that is appropriate to the marriage that has been done, namely by registering a marriage and obtaining a marriage certificate to facilitate the civil process in the family. This type of research is qualitative by discussing sociology and it was carried out using inductive analytical methods by discussing the issue of the implementation of marriage rights in the field and the implications of marriage rights to the status of marital power in terms of the system of agreement-invitation legislation. The results of this study are the implementation of the marriage certificate in the Jepara Religious Court has been carried out according to procedures that have been received and carried out by the Jepara Religious Court in accordance with the provisions of the procedural law of the religion in accordance with statutory provisions regulated by Law Number 50 Year 2009 concerning the Religious Courts.